Penerapan Aplikasi Flora Incognita untuk Meningkatkan Hasil Belajar Kognitif dan Kesadaran Tumbuhan Siswa SMA pada Materi Keanekaragaman Hayati - Soraya, Puan Helwa Rezha; Cahyani, Tasya Oktavia Regita; Hamdiyati, Yanti; Supriatno, Bambang (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
Indonesia has a high diversity of plant species, but the phenomenon of plant blindness is still often found among students, characterized by low awareness and mastery of the concept of biodiversity. This research aims to examine the effectiveness of the Flora Incognita application in increasing awareness of plants and the cognitive learning outcomes of high school students on biodiversity material. The research method used was pre-experimental with a one group pretest-posttest design. The research subjects were 10th grade students at one of the high schools in Cimahi City, West Java. The research results show that learning combined with technology in the form of the Flora Incognita application can improve students' cognitive learning outcomes with an N-Gain value of 0.5 in the medium category. Apart from that, this learning also increases awareness of plants with an N-Gain value of 0.3 in the medium category. Apart from that, no relationship was found between learning outcomes and plant awareness. This research concludes that the Flora Incognita application can be an innovative alternative to overcome the plant blindness phenomenon while increasing mastery of biodiversity material at the high school level.